Analysis of demographic, socio-economic and geographic factors affecting adoption and success of personal income tax e-filing in South Africa - Mathaba, Jeffrey Themba (Research of GSB, 2018)
E-filing of personal income tax returns is regarded as one of the South African Revenue Service (SARS)'s success stories based on its growth since its inception in 2006. Given the importance of tax revenue as a major source of revenue to government, this study explores the effects of personal income tax e-filling on tax compliance and tax revenues. The study was carried out with three objectives, namely; determining the relationship between personal e-filing growth and some demographic, socio-economic and geographic factors in South Africa; determining the relationship between personal income tax e-filing and personal income tax revenue; and determining the relationship between personal income tax e-filing and tax compliance. Descriptive statistics and the pooled ordinary least square were employed to analyse the data having found the absence of unit root at levels in the data. The study covered 6-year period prior to e-filing (2000-2005) and 10-year period of e-filing implementation from 2006 to 2015, with data collected from publicly available SARS database on registered taxpayers and revenues collected nationally and across South Africa's nine provinces and metropolitan areas. The results indicate that e-filing had a positive contribution to increase personal income tax revenue collection as well as tax compliance over the study period. The study concludes that the introduction of e-filling provided an opportunity for improved collection and compliance across the provinces of South Africa. We therefore recommend, among others, that investigations and investments in tax technology & e-filing in non-metropolitan areas be considered, and further research be done in identified areas of interest in South Africa and rest of the African continent.